Konsep Uang dan Kebijakan Moneter dalam Ekonomi Islam - Hasallyt, Nena (Master of Sharia Economics Program, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Monetary policy in Islamic economics is part of the branch of economics that discusses the nature, function and influence on economic activity in a country. Monetary policy can maintain economic stability, this can be seen by balancing the amount of money that is widely spread in a balanced way. If any money in circulation exceeds or is greater or less than a number of goods and services, then the economy in a country will be chaotic. The method of writing this article uses a qualitative research approach. The data analysis technique is in the form of descriptive analysis. Descriptive itself is a research result that is described as clearly as possible based on research